Pattern of dentoalveolar injuries in trauma patients presenting in maxillofacial department of tertiary care hospital - Ahmad Sohail; Jehan Alam; Ruqayah Shah; Sarfraz Ali (Medical Journal of South Punjab, 2024)
Objective: To determine the patterns of dentoalveolar injuries in patients presenting to the Maxillofacial Surgery Department of a tertiary care hospital.Methodology: The study employed a cross-sectional design and was conducted in the Department of Oral and Maxillofacial Surgery at Jinnah Postgraduate Medical Centre, Karachi, from December 2023 to June 2024. A detailed history and clinical examination, including extra-oral and intra-oral assessments, were conducted. Radiographic evaluations such as periapical, panoramic, and cone-beam CT scans were performed as needed. Injuries were classified according to Andreasen’s criteria.Results: Regarding the causes of nerve injury, road traffic accidents were the most common etiology, accounting for nearly half of the cases 49.7%, followed by assault 22.7%, falls 14.9%, epileptic seizures 9.4%, and firearm injuries 3.3%.The pattern of dentoalveolar injuries showed that enamel fractures were the most prevalent 24.9%, followed by root fractures 16.6%, subluxation and concussion 14.4%, dentine fractures 12.6%, extrusion 8.3%, crown fractures 6.6%, and intrusion 2.2%.Conclusion: Young males were predominantly affected by dentoalveolar trauma, with road traffic accidents and falls as the leading causes. Avulsion, subluxation, and luxation were the most common injury patterns.